A mindfulness intervention promoting work–life balance: How segmentation preference affects changes in detachment, well-being, and work–life balance - Sarah Elena Althammer; Dorota Reis; Sophie van der Beek; Laura Beck; Alexandra Michel (Journal of Occupational and Organizational Psychology, 2021)
This study evaluates a three-week online self-training intervention teaching mindfulness as a cognitive–emotional segmentation strategy. Daily effects on psychological detachment, affective well-being, psychological and strain-based work–family conflict, and satisfaction with work–life balance were assessed, with a particular focus on whether segmentation preferences moderate training responsiveness. A randomized wait-list control group design was used for administering daily questionnaires to 190 participants. Psychological detachment, affective well-being, and work–life interface measures were assessed daily. As expected, growth curve analyses revealed positive effects on psychological detachment, psychological work–family conflict, and work–life balance satisfaction. No effects were found for strain-based work–family conflict. Additionally, segmentation preferences moderated the intervention effect on psychological detachment, such that participants with low segmentation preference reported stronger intervention effects. Unexpectedly, affective well-being increased in both groups. Practitioner points Practicing mindfulness as a cognitive–emotional segmentation strategy enables detachment from work. Mindfulness training reduces psychological work–life conflict and enhances work–life balance satisfaction, irrespective of preferences for segmentation or integration. Mindfulness training increases detachment from work most successfully for integrators. Organizational practices and policies are advised to include brief mindfulness interventions in work–life balance programmes.
Keywords: 650; intervention; mindfulness; psychological detachment; segmentation preference; well-being; work–life balance